MOTIVAS KERJA KARYAWAN SALES & MARKETING DEPARTMENT DI TURI BEACH RESORT BATAM - Deni Ratna Sari; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Motivation is a condition that moves staff to be able to achieve the goals that havebeen determined. Based of theory Hergberz, a motivation influenced of motivatorfactor and hygiene factor. Therefore, the authors are interested to examine aboutwork motivation of staff sales & marketing department in Turi Beach ResortBatam.The sample used in this research is all staff of sales and marketing in TuriBeach Resort Batam which amounted to 8 people by using census samplingtechnique. This research uses quantitative descriptive method to categorize thedata then compiled by using frequency. And for data collection techniques in thisresearch using interviews, observation and questionnaires. By using Likert scalaas a measuring tool.Based on the result of research obtainted on work motivationof staff sales & marketing department in Turi Beach Resort Batam have highwork motivation. This is proved by the acquisition score total overall is 710points.Keywords :motivasi, motivator, hygiene, factor